Poetic Exploration of Obasa’s Prolegomenous Poetry - Duro Adeleke (Yoruba Studies Review)
Mere mentioning of poetics often ignites the memory of Aristotle whose admiration is hinged on the elegance and clarity of his style in poetics. Tis is as a result of the historic influence of poetics or aesthetics as well as the quality of its thought. Tus, poetics is not devoid of philosophical nuances. Based on this premise, an attempt is made here to explore the poetic strands in Obasa’s trilogy, wherein Yorubá proverbs are strung together. The paper, therefore, considers aesthetic category of artistic mimesis, intertextuality and components of all diction alongside stylistic elements because the principal task of poetics is to measure its legitimate domain in language. Tus, it is averred that literature depends on linguistic structure for its existence since language is the substance of literature (in our own instance, poetry). The essay adopts an eclectic theoretical approach since Obasa’s craftsmanship and subject-matter span an avalanche of forms and structures imbued with stylistic features. Primary data are largely drawn from his anthologies which facilitate the content analysis. In its findings, the paper has brought to the fore the fact that Obasa employed adaptation and mimesis in his presentation creatively, ̣ while different stylistic elements in his trilogy are replete with deviation. An attempt is made to bring into bold relief the suggestion that metaphor forms the hub of all other tropes that give grandeur to poetics in Obasa.